2022
DOI: 10.1155/2022/2490033
|View full text |Cite
|
Sign up to set email alerts
|

Innovation and Development of Cultural and Creative Industries Based on Big Data for Industry 5.0

Abstract: While art design is based on innovation and creativity, information technology is advancing by leaps and bounds for Industry 5.0. Big data technology has achieved breakthrough development, and the big data era that has followed has begun. Promoting the resources, technology, thinking big data is the general trend. It is an important expression of creative thinking, which is closely connected with art design and studies the relationship between design and art. As the starting point for research, the average gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 29 publications
(21 reference statements)
0
13
0
Order By: Relevance
“…China's "father of the creative industry," Li Wufeng, once put forward the theory that "scientific and technological innovation and cultural creativity are the twin engines of modern economic growth," raising the status of cultural creativity to the position of science and technology. Technology and art are equally important in the creative industry, and they are inseparable [15][16].…”
Section: Introductionmentioning
confidence: 99%
“…China's "father of the creative industry," Li Wufeng, once put forward the theory that "scientific and technological innovation and cultural creativity are the twin engines of modern economic growth," raising the status of cultural creativity to the position of science and technology. Technology and art are equally important in the creative industry, and they are inseparable [15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Given the existing problems, they proposed that we should cultivate talents for high-quality development of art and culture industries, pay attention to the digitalization of art, culture, and creative industries, and optimize the facilities of the Internet of Things [9]. Huang, L. et al proposed that big data technology can promote the development of resources, technology, and culture, which is closely related to art and culture as well as art design [10]. David, R. P. et al analyzed the impact of geographic and enterprise-level factors on the innovation of cultural and creative industries and cultural and creative industry companies by using a multi-level model, and the results showed that the impact of geographic and enterprise-level factors on the innovation of cultural and creative industries and cultural and creative industry companies is very important.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, this research study on transforming tang poetry into a designed and developed CAC product promotes product value. Huang and Jia (2022) highlight the importance of big data technology and its connection to art design in promoting innovation and growth in the industry. Tong (2021) focuses on the foreign trade aspect of Beijing's cultural and creative industry, identifying the small scale and need for diversified patterns.…”
Section: Introductionmentioning
confidence: 99%